2015
DOI: 10.4238/2015.july.13.10
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms in insulin-like growth factor-1 and risk of osteoporosis

Abstract: ABSTRACT. We conducted a case-control study to assess the relationship between rs35767, rs2288377, and rs5742612 insulin-like growth factor-1 (IGF-1) and osteoporosis risk in a Chinese female population. The genotypes of rs35767, rs2288377, and rs5742612 of IGF-1 were determined by polymerase chain reaction-restriction fragment length polymorphism. Patients with osteoporosis were more likely to have drinking and smoking habits and have lower bone mineral density in the L 2 -L 4 vertebrae, femoral neck, and tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…All of the studies were published in English. A total of 2807 participants took part in the studies, with 1 recruiting men and women, [ 25 ] and 3 women only. [ 23 , 24 , 26 ] Four studies investigated rs35767, [ 23 26 ] 3 studies assessed rs2288377, [ 23 25 ] and 3 studies evaluated rs5742612.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the studies were published in English. A total of 2807 participants took part in the studies, with 1 recruiting men and women, [ 25 ] and 3 women only. [ 23 , 24 , 26 ] Four studies investigated rs35767, [ 23 26 ] 3 studies assessed rs2288377, [ 23 25 ] and 3 studies evaluated rs5742612.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2807 participants took part in the studies, with 1 recruiting men and women, [ 25 ] and 3 women only. [ 23 , 24 , 26 ] Four studies investigated rs35767, [ 23 26 ] 3 studies assessed rs2288377, [ 23 25 ] and 3 studies evaluated rs5742612. [ 23 25 ] The pooled minor allele frequency for rs35767, rs2288377, rs5742612 was 0.291 (95% CI: 0.275–0.308), 0.100 (95% CI: 0.088–0.113), and 0.131 (95% CI: 0.118–0.146), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Uthra et al . investigated the role of cytosine-adenine (CA) [ 17 , 18 ] repeats in IGF1 promoter region in DR development based on a Southern Indian cohort. The study showed that CA [ 18 ] repeats genotype was a risk factor of DR [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, single nucleotide polymorphism (SNP) has become an important mean of revealing the susceptibility of individuals to some diseases. IGF1 protein encoded gene, IGF1 is located on chromosome 12q22-23 [ 16 ] and consisted of 5 exons and 4 introns, including a number of SNPs [ 17 , 18 ]. However, few studies referred to the association between IGF1 SNPs and DR occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of IGF-I deficiency has been confirmed in humans, in which patients with a mutant IGF-IR show growth retardation both before and after birth, and a mutant IGF-I gene can lead to significantly decreased BMD (Camacho-Hübner et al, 2002; Walenkamp et al, 2005; Walenkamp and Wit, 2007). Furthermore, a recent study showed a significant association between polymorphisms in the IGF-I gene and risk of osteoporosis in a population of Chinese women (Zhang et al, 2015). Thus, both GH and IGF-I are key regulators of peak bone mass acquisition in animals and in humans.…”
Section: Gh/igf Effects On Bonementioning
confidence: 99%